Pharmacological Assessment of Aqueous Ethanolic Extract of Against Haloperidol-Induced Parkinson's Like Symptoms in Animal Model: A Dose-Dependent Study With Mechanistic Approach - Jiangyu Han; Xu Hao; Mishal Fatima; Zunera Chauhdary; Ayesha Jamshed; Hafiz Muhammad Abdur Rahman; Rida Siddique; Muhammad Asif; Saba Rana; Liaqat Hussain (SAGE Publishing, 2024)
Introduction: Parkinson's disease (PD) is characterized by dopamine deficiency in the corpus striatum due to the degeneration of dopaminergic neurons in the substantia nigra. Symptoms include bradykinesia, resting tremors, unstable posture, muscular rigidity, and a shuffled gait. Thalictrum foetidum is traditionally used for neurodegenerative disorders. Objectives: This study aimed to explore the therapeutic potential of aqueous ethanolic extract of Thalictrum foetidum (AETF) against Parkinson-like symptoms and to investigate its underlying mechanism. Methodology: Thirty-six albino mice were randomly divided into 6 groups (n = 6): normal control, disease control, standard treatment (levodopa/carbidopa, 100/25 mg/kg), and 3 treatment groups (AETF at 200, 400, and 600 mg/kg). One hour before treatment, haloperidol (1 mg/kg, i. p .) was administered to induce Parkinson's disease in all groups except the normal control group. Results: Behavioral analysis showed significant improvement ( P < .001) in motor function, muscular coordination, and reduced muscular rigidity and tremors. AETF also reduced oxidative stress. Histological examination of the brain showed reduced Lewy bodies, neurofibrillary tangles, and plaque formation. Conclusion: AETF alleviated PD symptoms by reducing neurodegeneration, modulating oxidative stress, and inhibiting the expression of nuclear factor-κB (NF-κB) and associated inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6).